2023
DOI: 10.2478/emj-2023-0015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality perception of public services: customer-oriented approach

Abstract: The focus of this research is on assessing the perception of public service quality through a customer-centred approach. Public service quality comprises multiple factors that are prioritised differently by customers. Therefore, the study aims to conduct a literature review to identify the primary quality dimensions of public services and evaluate the heterogeneity of their perception within the context of Lithuania. The research measures the user perceptions of public service quality. The literature review al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Recently, Butkus et al (2023), in a specific study for the context of public services, found that (1) there is no unified, systematic, and standardized approach to evaluating the quality of public services;…”
Section: Reasons To Create a New Scalementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Butkus et al (2023), in a specific study for the context of public services, found that (1) there is no unified, systematic, and standardized approach to evaluating the quality of public services;…”
Section: Reasons To Create a New Scalementioning
confidence: 99%
“…Furthermore, in several attempts to apply SERVQUAL or SERV-PERF to the public service context, the need for adaptation and creation of items is clearly observed (Akdere et al, 2020;Butkus et al, 2023;Dung, 2021;Jou et al, 2023;Maagi & Mwakalobo, 2023;Moura e Sá et al, 2021;Sharma & Al Sinawi, 2021;Sohail & Hasan, 2021). Some examples among the various proposed indicators are those related to transparency (Lim & Lee, 2021;López-Lemus, 2023;Tanny & Zafarullah, 2023;Witesman et al, 2022), doing the right thing for the country (Ali AlShehail et al, 2022;Bucaite Vilke & Vilkas, 2018;Chien & Thanh, 2022;López-Lemus, 2023;Tanny & Zafarullah, 2023), and civil servants' ethics and capacity (Chien & Thanh, 2022;López-Lemus, 2023;Tanny & Zafarullah, 2023).…”
Section: Reasons To Create a New Scalementioning
confidence: 99%
See 1 more Smart Citation